2022
DOI: 10.32604/phyton.2022.016397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Radiation and Other Abiotic Stress Factors on DNA of Different Wild Plant Species Grown in Three Successive Seasons in Alpine and Subalpine Regions

Abstract: Plants in natural ecosystems are exposed to a combination of UV radiation, ionizing radiation (IR) and other abiotic factors. These factors change with the altitude. We investigated DNA alterations of some wild plants of different plant families in natural ecosystems at three altitudes in Rila Mountain, Bulgaria (1500, 1782, and 2925 m above sea level (a.s.l.) exposed to UV radiation, IR and other abiotic stresses, to assess the tolerance of plant species to the changing environmental conditions in three succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In our previous three years study (from 2017 to 2019) it was found that the increase in the intensity of UV radiation with height is clearly visible [13]. Based on our previous data for UV parameters for period of 2017-2019 it could be suggested that change of UV irradiation for one year is insignificant (about 1%).…”
Section: Radiation Conditions At Experimental Sitesmentioning
confidence: 83%
See 1 more Smart Citation
“…In our previous three years study (from 2017 to 2019) it was found that the increase in the intensity of UV radiation with height is clearly visible [13]. Based on our previous data for UV parameters for period of 2017-2019 it could be suggested that change of UV irradiation for one year is insignificant (about 1%).…”
Section: Radiation Conditions At Experimental Sitesmentioning
confidence: 83%
“…Information for these parameters was obtained from the SoDa database (provider: MINES ParisTech/Armines/Transvalor (France) (http://www.soda-pro.com) derived from broadband HelioClim-3 v5 Solar Irradiance (satellite data). Average daily values for five successive months (May, June, July, August and September) are calculated [13].…”
Section: Radiation Conditions At Experimental Sitesmentioning
confidence: 99%
“…Our previous study showed a visible tendency to increase the intensity of UV radiation with height for a period of three years (2017-2019) [9]. It was suggested that the change in UV irradiation for one year is insignificant (about 1%).…”
Section: Radiation Conditions At the Experimental Sitementioning
confidence: 94%
“…Across a diversity of plant species from alpine and subalpine zones in Bulgaria, improved photoprotection has been found to effectively prevent greater DNA damage caused by increased UV radiation at higher altitudes. These mechanisms were sufficiently effective since plants growing at the highest elevations had fewer UV-induced DNA dimers than those at lower elevations, with grasses (Family Poaceae) least susceptible to UV-induced DNA damage among a wide diversity of plant families tested [ 249 ]. Nevertheless, as species migrate to high elevations, more resources may be allocated towards protection against UV radiation, and this could in turn divert resources away from growth, which could then reduce competitive ability [ 250 , 251 ].…”
Section: Species Distributions and Biodiversitymentioning
confidence: 99%